The Importance of the mineral coal in the development - León Delgado, Elard Felipe (2006)
In the future, the industry can be determined by processes of low cost operation and the capital. The reliability and low price of the mineral coal are the factors for the utilization in the industry. The coal mineral can be use many and several activities. The implacable pressure on the costs of operation, production and investment costs is forcing the producers of steel to accelerate the technological development and to considering new technologies and improvement, with a perspective to get the best qualities, best performance, with less intensity of capital and minor environment impact. The utilization of the mineral coal is an alternative.